Bral1: its role in diffusion barrier formation and conduction velocity in the CNS - Bekku, Yoko; Vargová, Lýdia; Goto, Yoshinobu; Voříšek, Ivan; Dmytrenko, Lesia; Narasaki, Masahiro; Ohtsuka, Aiji; Fässler, Reinhard; Ninomiya,Yoshifumi; Syková, Eva; Oohash, Toshitaka (The Journal of neuroscience, 2010)
At the nodes of Ranvier, excitable axon membranes are exposed directly to the extracellular fluid. Cations are accumulated and depleted in the local extracellular nodal region during action potential propagation, but the impact of the extranodal micromilieu on signal propagation still remains unclear. Brain-specific hyaluronan-binding link protein, Bral1, colocalizes and forms complexes with negatively charged extracellular matrix (ECM) proteins, such as versican V2 and brevican, at the nodes of Ranvier in the myelinated white matter. The link protein family, including Bral1, appears to be the linchpin of these hyaluronan-bound ECM complexes. Here we report that the hyaluronan-associated ECM no longer shows a nodal pattern and that CNS nerve conduction is markedly decreased in Bral1-deficient mice even though there were no differences between wild-type and mutant mice in the clustering or transition of ion channels at the nodes or in the tissue morphology around the nodes of Ranvier. However, changes in the extracellular space diffusion parameters, measured by the real-time iontophoretic method and diffusion-weighted magnetic resonance imaging (MRI), suggest a reduction in the diffusion hindrances in the white matter of mutant mice. These findings provide a better understanding of the mechanisms underlying the accumulation of cations due to diffusion barriers around the nodes during saltatory conduction, which further implies the importance of the Bral1-based extramilieu for neuronal conductivity.
Keywords: centrální nervový systém; kationty; Hyaluronic Acid; Diffusion Magnetic Resonance Imaging; Mice; zvířata; buněčná membrána; kyselina hyaluronová; difuzní magnetická rezonance; myši knockoutované; proteoglykany; Central Nervous System; Ion Channels; nervová vlákna myelinizovaná; Ranvier's Nodes; mužské pohlaví; Action Potentials; Ion Channel Gating; extracelulární matrix; Cell Membrane; iontové kanály; Proteoglycans; gating iontového kanálu; myši inbrední ICR; Cations; Mice, Inbred ICR; Nerve Fibers, Myelinated; Ranvierovy zářezy; Mice, Knockout; Nerve Tissue Proteins; Neural Conduction; myši; ženské pohlaví; Female; nervové vedení; Animals; Extracellular Matrix; proteiny nervové tkáně; Male; difuze; akční potenciály; Diffusion